A national force : the evolution of Canada's army, 1950-2000 - Kasurak, Peter, 1949- (Studies in Canadian military history, 2013)
Canadians consider the period between the Second World War and the unification of the armed services in 1968 as a "golden age," a time when their army dropped the shackles of its imperial past and emerged as a truly national peacekeeping force. In this landmark book, Peter Kasurak draws on recently declassified documents to show that this era was in fact clouded by the army's failure to loosen the grasp of British army culture, produce its own doctrine, and advise political leaders effectively. The discrepancy between the army's goals and the Canadian state's aspirations as a peacemaker in the postwar world resulted in a series of civilian-military crises that ended only when the scandal of the Somalia Affair in 1993 forced reform. Kasurak offers an illuminating account of the organizational growing pains that wracked the Canada's army as it evolved into a force that could reflect the aspirations of both its country and military leadership.